Allergic contact dermatitis systemically induced by inhalation of mercury vapor -baboon syndrome-. - Chieco, P.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2008)
Baboon syndrome is a systemically induced allergic contact dermatitis, usually associated in children with a previous sensitization to mercury and triggered by inhalation of mercury vapor from a broken thermometer. Here are reported two cases in children without a previous history of localized dermatitis, but with proven sensitization to mercury.